2009
DOI: 10.1109/jsen.2009.2030974
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Embedded Resonant Pressure Sensor Fabricated in the Standard LTCC Technology

Abstract: This paper proposes a fully embedded resonant pressure sensor operating in the MHz range and realized in the standard low-temperature co-fired ceramics (LTCC) technology. Buried sensor design and usage of LTCC materials enable application of this sensor in high-temperature and chemically aggressive environments. Upgraded sensor and sensor-antenna models residing on an analytical concept are used for prediction of the system performance. Also, simulation results show that an increase of Young's modulus for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 12 publications
0
45
0
1
Order By: Relevance
“…Radosavljevi et al have reported an LTCC-based wireless pressure sensor for use in chemically aggressive environments [23]. The sensor is a fully embedded LC resonating circuit, and consists of a cavity having both a top and a bottom diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Radosavljevi et al have reported an LTCC-based wireless pressure sensor for use in chemically aggressive environments [23]. The sensor is a fully embedded LC resonating circuit, and consists of a cavity having both a top and a bottom diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Beside of these simplest examples, pressure sensors are also popular [16][17][18][19][20]. The high piezoresistive effect seen in thick-film resistors enables the fabrication of LTCC piezoresistive force sensors [20] or uniaxial accelerometers [21].…”
Section: Introductionmentioning
confidence: 99%
“…LTCC has the additional benefit compared to HTCC that it allows the use of high conductivity metals like gold, silver and copper, which are essential for low loss microwave and millimeter-wave passive elements. The applications of LTCC technology are not limited to electronic packaging but also include MEMS packaging, microfluidics [10][11][12], sensors, actuators [13][14][15], etc. Thus, technological advancement in LTCC technology benefits multiple fields and the integration of high frequency components is key for realizing a wide range of wireless sensing systems -particularly in harsh environments where ceramic materials have a significant advantage over organic-based substrate materials.…”
Section: Introductionmentioning
confidence: 99%